Powder Flow Tester (PFT): a new tool to evaluate wheat flour dough behavior by measuring unconfined failure strength under variable consolidation stresses - Ermis, Ertan; Yasasin, Merve; Bozkurt, Fatih; Yilmaz, Mustafa Tahsin (SPRINGER, 2018)
In this study, Powder Flow Tester (PFT) was firstly used to determine and better understand the behavior of different dough samples. For this purpose, four different wheat flours with varying strengths in addition to flour samples having varied salt concentrations were tested using PFT and the data obtained were compared with the data obtained by extensograph and with the ones reported in previous studies. As a result, the dough samples tested exhibited different failure strenghts ranging from 0.5 to 3.5 kPa under applied consolidation stresses ranged from 0.5 to 5.5 kPa. The resistance (R-50) values obtained from extensograph from strong to weak flour samples were noted as 453, 410, 312 and 149 BU. Same order of failure strength values were derived from PFT (around 1.75, 1.50, 1.25 and 1.00 kPa) while the extensibility properties differed. This study shows that, PFT seems to be an interesting piece of equipment to better understand dough's responses to deformations and may offer a new insight into the characterization of the dough strength and quality which are important characteristics in dough processing in food industry.
Keywords: Dough rheology; Dough extension; Wheat flour; Gluten; Powder flow tester; LARGE-DEFORMATION; RHEOLOGICAL PROPERTIES; BREAD DOUGH; EXTENSIONAL RHEOLOGY; QUALITY; MICROSTRUCTURE; BREADMAKING; CHICKPEA; Food Science & Technology